Spiritual Leadership on Proactive Workplace Behavior: The Role of Organizational Identification and Psychological Safety - Chen, Silu; Jiang, Wanxing; Zhang, Guanglei; Chu, Fulei (Frontiers in Psychology, 2019)
This study investigates whether and why spiritual leadership may contribute to enhanced proactive employee workplace behavior. Based on self-determination theory (SDT), we examine the effects of two sequential mediators (i.e., organizational identification and psychological safety) on the relationship between spiritual leadership and proactive workplace behavior. Data collected from 188 subordinate-leader dyads in Chinese firms suggested that spiritual leadership has a significant positive effect on proactive workplace behavior. In addition, both organizational identification and psychological safety mediate the relationship between spiritual leadership and proactive workplace behavior. Furthermore, spiritual leadership positively influences organizational identification, and such identification nurtures psychological safety, which, in turn, fosters the proactive behavior of employees. It extends the existing impact of spiritual leadership to proactive workplace behavior and shed lights on the mediating mechanisms through which spiritual leadership exerts influences on proactive workplace behavior. Finally, it considers the important roles played by leaders in modern organizations.